Analisis Pemahaman Pola Hidup Sehat Sebagai Sarana Penginjilan di Jemaat Sion Student Hill Side Airmadidi - Sukardi, Josua; Hutagalung, Stimson (Peneliti.net, 2024)
Healthy lifestyle is very important in maintaining human body health. This lifestyle is acquired by those who pay attention to their body conditions. Looking at the current world situation, many people are found to suffer from the consequences of unhealthy lifestyle habits. Understanding the importance of a healthy lifestyle will help everyone understand the importance of maintaining health, and through understanding healthy lifestyle habits, it can be a means for evangelism where health is used as a tool to introduce the gospel. The method used in this writing is qualitative method and questionnaires will be distributed to church members to obtain understanding of healthy lifestyle among church members. The research problem formulation is as follows: 1. What is the importance of a healthy lifestyle?; 2. How is the understanding of healthy lifestyle among the members of Sion Student Hill Side Airmadidi Church?; 3. How can the understanding of healthy lifestyle help the members of Sion Student Hill Side Airmadidi Church in evangelism? Implementing a healthy lifestyle is a continuous and regular series of activities, thus becoming a habit in lifestyle.